The Development of a PTSD Standardized Patient Encounter - Jessica Doolen; Gigi Guizado de Nathan; Michael Johnson; Cheryl Perna; Michelle Giddings (Association of American Medical Colleges, 2015)
Abstract Introduction The Liaison Committee on Medical Education's new accreditation standards recommend that medical education must prepare medical students to learn to collaborate with other healthcare professions. This post-traumatic stress disorder (PTSD) standardized patient (SP) case answers this call to collaborate with health care professions to better prepare new graduate nurses to enter multidisciplinary professional practice. Methods This resource provides an SP case specifically about PTSD, which includes a flashback in response to stimuli during the encounter, thus allowing students the opportunity to recognize an impending PTSD attack and offer ways to interrupt an impending attack. A simulated hospital suite was modified to mimic an inpatient clinic room. The encounter was digitally recorded for review in debrief. Each SP simulation was allowed to run a maximum of 20 minutes with a warning announcement being delivered at the 15-minute mark to cue the students to close the encounter. Faculty or students could end the scenario before the full 20 minutes if the learning objectives were successfully achieved. At the end of the scenario, the SP had a maximum of 15 minutes to come out of character, review the guidelines for debrief, and collect his relevant thoughts for feedback comments. Once this was completed, the SP joined the nursing students and faculty in debrief and engaged in guided reflection on the encounter by giving positive and meaningful feedback to the students. At the end of the debrief session, nursing students completed a web-based evaluation of the SP encounter. Results Results were overwhelmingly positive, with the majority of the undergraduate nurse students (n = 40) agreeing or strongly agreeing the SP encounter was an effective learning experience. Students' comments indicated that the interaction with the SP rewarded caring relationship strategies, helped them to develop a therapeutic relationship with the patient, and gave them an opportunity to demonstrate empathy for a patient with PTSD. Discussion This resource adds to MedEdPORTAL's collection of interprofessional teaching/learning strategies, while focusing on veterans' health, which is a national healthcare concern and a priority for nursing education. During the case, the SP's PTSD characteristics escalate and/or de-escalate based on establishment of a caring relationship by the student. This dynamic interaction is more effective than a lecture or reading, as illustrated by the learner and SP comments.